Case Report: MDFIC gene mutation resulting in central conducting lymphatic anomaly facilitates group A Streptococcus sepsis - Weidner, Johannes; Fiedler, Kai; Schulze-Becking, Mechthild; Sentner, Christiaan Peter; Korenke, Christoph; Heep, Axel (Frontiers in Pediatrics, 2024)
Background: Central conducting lymphatic anomaly (CCLA) is a heterogeneous disorder, characterized by structural anomalies of the main collecting lymphatic vasculature. These result in chronic chylous leaks, such as congenital hydrothorax, potentially impairing the normal immune response. Recently, MyoD family inhibitor domain-containing (MDFIC) gene mutations have been identified as a cause of CCLA. Group A Streptococcus infections are common and timely identification of patients at risk for severe complications is crucial.Here we present a 13-year-old female patient with CCLA associated with a MDFIC mutation suffering from a severe group A Streptococcus sepsis. The patient was initially unresponsive to aggressive fluid resuscitation. Although the course of the sepsis was severe, standardized treatment according to the surviving sepsis campaign proved effective in stabilizing the patient.Discussion: The patient´s MDFIC mutation may have been a contributing factor for the severe clinical course of the sepsis. It is theorized that the mutation has direct and indirect effects on the function of the immune system, indirectly as the cause of CCLA and directly by potentially influencing transcriptional activity in immune cells. More research on the effect of MDFIC mutations on immune responses is required.